THE MAGHRIBIAN IMMIGRANTS' SITUATION IN MURCIA: A PSYCHOSOCIAL ANALYSIS - Paterna Bleda, Consuelo (Anales de Psicología / Annals of Psychology)
In this paper are analyzed the psychosocial factors which are conceptualiced the situation of a Mogrebian immigrants. A contents analysis is made with the data, and the Social Identity Theory is discussed because your participation in the explanation of identity group processes.